How to improve trade relations between Portugal and Russia - Mohammad, Amr (2021)
Despite the long-standing cooperation between Portugal and Russia, the current bilateral trade values do not commensurate the two and a half decades of cooperation. The current trade values trend based on data between 2006 and 2019 shows somewhat unstable trade relations characterized by both rising and falling in different years. While different scholars have explored the challenges that should be addressed, such as trade protectionism and opportunities that can be exploited to enhance trade relations, there still exists a gap in literature exploring various measures that can be employed to improve the Russian-Portuguese trade relations. Therefore, this research aims to explore the current situation in the trade relations between Russia and Portugal and also the measures that can be employed to improve the international trade standing between the two countries. Analysis of data from secondary sources shows that Portugal and Russia have traded for approximately 240 years. Russia mainly sells crude oil products and farm inputs to Portugal, while Portugal mainly provides agricultural commodities to Russia. The key success factors required to improve the Russian-Portuguese trade relations include favorable trade policies, increased foreign direct investment, and preferential bilateral agreements. Presently, there is a mismatch between Russia's and Portugal’s trade policies, whereby Russia is more protectionist than Portugal. Moreover, there is only one identifiable bilateral trade agreement whose impact on countries’ trade relations is remote. The level of foreign direct investment is still low to impact trade relations between Russia and Portugal. This study proposes a three-fold strategy to improve Russian-Portuguese trade relations. Firstly, the relaxation of trade policies such as ease of trading across the border, tariffs, and economic freedom is necessary. Secondly, the nations should take measures to boost the level of foreign direct investment amongst them. Thirdly, preferential trade agreements are necessary to address the trade barriers and position the countries as strategic trade and investment partners.